The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/jvi.80.6.2641-2653.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Evolution of Vaccine-Derived Polioviruses: Changes in Individual Epitopes and Relative Stability of the Overall Immunological Properties

Abstract: The Sabin oral poliovirus vaccine (OPV) readily undergoes changes in antigenic sites upon replication in humans. Here, a set of antigenically altered descendants of the three OPV serotypes (76 isolates) was characterized to determine the driving forces behind these changes and their biological implications. The amino acid residues of OPV derivatives that lie within or close to the known antigenic sites exhibited a marked tendency to be replaced by residues characteristic of homotypic wild polioviruses, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 65 publications
7
34
2
Order By: Relevance
“…The majority of these AD isolates appeared to be derived from the mOPV1 challenge dose provided at the age of 28 days. Replacement of lysine 60 in the VP3 capsid region, as described by previous studies, explains the AD character observed in this study (3,42). This residue is located in the loop of antigenic site III and is also involved in the interaction between the virus and the cellular receptor CD155 (2,22).…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…The majority of these AD isolates appeared to be derived from the mOPV1 challenge dose provided at the age of 28 days. Replacement of lysine 60 in the VP3 capsid region, as described by previous studies, explains the AD character observed in this study (3,42). This residue is located in the loop of antigenic site III and is also involved in the interaction between the virus and the cellular receptor CD155 (2,22).…”
Section: Resultssupporting
confidence: 49%
“…This residue is located in the loop of antigenic site III and is also involved in the interaction between the virus and the cellular receptor CD155 (2,22). This effect was compensated for in one strain by an additional mutation of Ala 59 to valine as shown previously (42).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Since the receptor-recognizing regions of the capsid proteins overlap the regions comprising immunodominant viral epitopes, acquisition of certain attenuating mutations was accompanied by vaccine-specific alterations in antigenic properties. Thus, the appearance of "non-Sabin-like" antigenic characteristics typical of most VDPV is believed to be due to two independent processes, immune pressure and loss of fitness-decreasing capsid mutations (27). However, the examples of PV2/Bel and PV2/Rus demonstrate that elimination of antigenicity-changing and fitness-decreasing capsid mutations is not an obligatory component of extended OPV evolution.…”
Section: Vol 83 2009mentioning
confidence: 99%
“…In polioviruses, the major epitopes are thought to involve predominantly amino acid residues 91 to 102 of VP1 (antigenic site 1 or AgS1), residues 221 to 226 of VP1, 164 to 170 and 270 of VP2 (AgS2), residues 58 to 60 and 71 to 73 of VP3 (AgS3), and residues 72 of VP2 and 76 of VP3 (AgS4) (16). Of these positions, only Ala-101 was changed to Thr in PV2/Rus, but mutation at this position was previously shown not to alter the Sabin-like enzyme-linked immunosorbent assay response (27).…”
Section: Vol 83 2009mentioning
confidence: 99%